Modified biophysical profile and perinatal outcome in high risk pregnancies - Anjum, Gulafshan; Mittal, Hina; Chauhan, Nidhi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Aim and objective of current investigation was to evaluate perinatal outcome in high risk pregnancy with modified biophysical profile and also evaluate the efficacy of MBPP. Methods: Type of study was observational study, 100 patient fulfilling inclusion criteria were included in study. All women were subjected to modified biophysical profile comprises amniotic fluid index and non stress test. NST was performed with cardiotocogram, real time ultrasound scanning was performed. Perinatal outcome assessed in terms of admission to NICU, low birth weight, foetal distress, low APGAR score, neonatal mortality. Results: Out of 100 cases, 55 cases had reactive NST and 45 had non reactive NST. AFI was normal in 79 cases 21 cases had abnormal AFI. Diagnostic power was maximum seen with NST i.e. 76.36% (61.90% for AFI and 71.64% for combined MBPP) it indicates that NST is a good predictor to diagnose a compromised foetus. Conclusions: This study shows that pregnancy with high risk factors are associated with more chances of intrapartum complications perinatal morbidity and mortality , if MBPP was abnormal or any one parameter was abnormal, chances of perinatal morbidity were high.